DINAMIKA INDUSTRI GULA SEJAK CULTUURSTELSEL HINGGA KRISIS MALAISE TAHUN 1830 - 1929 - Yusuf Perdana; Henry Susanto; Yustina Sri Ekwandari (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This research aims to analyze the history of the sugar industry in the Dutch East India during the period 1830-1929, the impact of the cultuurstelsel on the sugar industry, the implementation of the 1870 agrarian law, and the impact of the economic crisis on the production of the sugar in the East India. The method used in this study is the historical method, Including heuristics or collection of sources, source criticism or reviewing the truth of existing sources, interpretation of data or historical interpretation, and historiography or the preparation of qualitative descriptions that can be justified. In this research it was explained that the sugar industry in Dutch East India during the period 1830 to 1929 growth fastly. Even the period 1840-1849 the sugar industry occupied the second largest profit after coffe. The enactement of the agrarian law in 1870 had a impact on the entry of foreign capital which resulted in a drastic increase in sugar production in the Ducth East India to become one of the largest sugar exporters in the world. World War I caused economic chaos and the decline of the New York stock market resulted in a slowdown in the market, especially the sugar industry, known as the malaise crisis. The Malaise crisis has caused the sugar industry to reduce its production drastically and have an effect on the migration of plantation workers to other regions and shift to industrial and service sectors.